2016
DOI: 10.1177/1054773816682331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Childbirth Education Classes in Turkey on Adaptation to Pregnancy Process, Concerns About Birth, Rate of Vaginal Birth, and Adaptation to Maternity: A Case-Control Study

Abstract: This study aims to examine the impact of childbirth education in Turkey on the adaptation to pregnancy process, concerns about birth, rate of vaginal birth, and adaptation to maternity. This quasi-experimental study with control group was conducted from December 2013 to December 2014. The sample size was 132 primiparous pregnant women ( n = 66, n = 66). The average age of the pregnant women in the experimental and control groups was 24.41 ± 3.92 and 23.68 ± 4.19, respectively. The study showed that experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…The results of all these studies concur with the present findings. Teaching topics such as changes during pregnancy, signs of onset of labor and non-medicinal pain relief techniques can help reduce women's prenatal anxiety [3,5,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of all these studies concur with the present findings. Teaching topics such as changes during pregnancy, signs of onset of labor and non-medicinal pain relief techniques can help reduce women's prenatal anxiety [3,5,21].…”
Section: Discussionmentioning
confidence: 99%
“…The total score of this questionnaire is the sum of the scores of all the items, and ranges from 0 to 165, and higher scores suggest greater fear of childbirth. Items 2,3,6,7,8,11,12,15,19,20,24,25,27, and 31 are scored in reverse. Wijma et al determined the reliability of the questionnaire by the split-half Fig.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these classes, they are provided with information and trained to perform physical exercises and to improve their self-control capabilities, which may increase their satisfaction with the delivery experience [15,16]. These classes can also help women quickly recognize the signs and symptoms of postpartum depression [17], and increase women's understanding of childbirth in order to better meet their needs [18]. However, lack of awareness and/or provision of inconsistent or contradictory information in these classes can lead to negative childbirth experiences [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In 1960s, Lamaze introduced prenatal maternal education and active participation of mothers in the childbirth process to emphasize natural birth without unnecessary interventions [6,7]. The results of empirical studies, demonstrated that women who participated in childbirth preparation classes managed to adapt better to labor pain, used fewer labor medicines, and had fewer instrumental deliveries [8][9][10]. Today, women tend to manage their own labor, control their delivery, use non-pharmacological pain management techniques, and experience a good delivery by sharing this special experience with their family [11].…”
Section: Introductionmentioning
confidence: 99%